Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Intimately tracking NO2 pollution over the New York City - Long Island Sound land-water continuum: An integration of shipboard, airborne, satellite observations, and models - Maria Tzortziou; Christopher P. Loughner; Daniel L. Goldberg; Laura Judd; Dilchand Nauth; Charlotte F. Kwong; Tong Lin; Alexander Cede; Nader Abuhassan (Science of The Total Environment, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer - Inga K. Koerte; Roald Bahr; Peter Filipcik; Jolien Gooijers; Alexander Leemans; Alexander P. Lin; Yorghos Tripodis; Martha E. Shenton; Nir Sochen; Stephan P. Swinnen; Ofer Pasternak (Brain Imaging and Behavior, 2022)
Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RHI, or about the risk factors that may lead to clinical or behavioral sequelae. REPIMPACT is a prospective longitudinal study of competitive youth soccer players and non-contact sport controls aged 14 to 16 years. The study aims to characterize consequences of exposure to RHI with regard to behavior (i.e., cognition, and motor function), clinical sequelae (i.e., psychiatric and neurological symptoms), brain structure, function, diffusion and biochemistry, as well as blood- and saliva-derived measures of molecular processes associated with exposure to RHI (e.g., circulating microRNAs, neuroproteins and cytokines). Here we present the structure of the REPIMPACT Consortium which consists of six teams of clinicians and scientists in six countries. We further provide detailed information on the specific aims and the design of the REPIMPACT study. The manuscript also describes the progress made in the study thus far. Finally, we discuss important challenges and approaches taken to overcome these challenges.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

Rapid decrease in tumor perfusion following VEGF blockade predicts long-term tumor growth inhibition in preclinical tumor models - Alexandra Eichten; Alexander P. Adler; Blerta Cooper; Jennifer Griffith; Yi Wei; George D. Yancopoulos; Hsin Chieh Lin; Gavin Thurston (Angiogenesis, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)